Comparison of the composition of faecal fluid in Crohn's disease and ulcerative colitis. Issue 4 (April 1982) - Schilli, R; Breuer, R I; Klein, F; Dunn, K; Gnaedinger, A; Bernstein, J; Paige, M; Kaufman, M
Abstract : We determined the ionic composition of faecal fluid from 13 patients with Crohn's disease limited to the colon, 10 with diffuse ulcerative colitis, and eight with ulcerative proctitis. The Crohn's and colitis groups had similar proportions of colon surface involved radiographically and similar 24 hour faecal weights. However, Crohn's patients' faecal fluid had arithmetically lower mean sodium and statistically lower mean chloride (34.8 mmol/l +/- 16.2 SD vs. 53.1 mmol/l +/- 23.1 SD) and higher potassium (49.2 mmol/l +/- 20.2 SD vs. 33.0 mmol/l +/- 13.8 SD) concentrations (p less than 0.05 for each) and much higher osmolality (487.1 mOsmol/kg +/- 87.1 SD vs. 341.1 mOsmol/kg +/- 88.9 SD, p less than 0.001). Separation of these patients using the faecal osmotic gap agreed with the clinical classification in 86% of cases. The diarrhoea of proctitis patients had a nearly normal ionic composition which was clearly distinguishable from that of diffuse colitis. These results suggest differences in the composition and perhaps the pathogenesis of the diarrhoea of Crohn's and ulcerative colitis. The composition of fluid may prove a useful, non-invasive method for classifying patients with inflammatory bowel disease and, in ulcerative colitis, determining the extent of the inflammatory process.